Two polymolybdate-directed Zn(ii) complexes tuned by a new bis-pyridine-bis-amide ligand with a diphenylketone spacer for efficient ampere sensing and dye adsorption. Issue 29 (6th July 2022) - Wang, Xiu-Li; Zhang, Yue; Chen, Yong-Zhen; Wang, Yue; Wang, Xiang
Abstract : Two polymolybdate-based Zn(ii ) complexes were constructed from a new bis-pyridine-bis-amide ligand, which can be used as electrocatalysts and electrochemical sensors for Cr(vi ), KBrO3, H2 O2 and AA, and exhibit selective adsorption of CV and MB. Abstract : By introducing a new semi-rigid bis-pyridine-bis-amide ligand with diphenylketone as a spacer, 4, 4′-bis(4-pyridinecarboxamide)phenylketone(L), two polymolybdate-based metal–organic complexes (MOCs), namely, [ZnL(MoO4 )] (1 ) and (H2 L)4 [Zn(CrMo6 (OH)6 O18 )2 (H2 O)4 ][ZnL2 (CrMo6 (OH)6 O18 )2 (H2 O)2 ]·8H2 O (2 ), were successfully assembled via a solvothermal method. Complexes 1 and 2 show different structures by introducing different Anderson-type [TeMo6 O24 ] 6− /[CrMo6 (OH)6 O18 ] 3− polyoxoanions in the H2 O–EtOH mixture solvent, including the 3D network of 1 and the 0D supramolecular structure of 2 . An interesting structural feature in 1 is that an inorganic ZnMoO4 n layer could be formed, although an A-type [TeMo6 O24 ] 6− polyoxoanion was utilized as the raw material. Noteworthily, complexes 1 and 2 can be employed as dual-function electrocatalysts for the electroreduction of Cr(vi ), KBrO3, and H2 O2 and the electrooxidation of ascorbic acid (AA). They can also be used as electrochemical sensors for the quantitative detection of Cr(vi ), KBrO3, H2 O2, and AA; in particular, low detection limits (0.033 μM for 1 and 0.037 μM for 2 ) were observed for Cr(vi ) ions. Complex 2 shows a rapid and highly selective adsorption activity for the organic dyes crystal violet and methylene blue.